2020
DOI: 10.3390/ma14010165
|View full text |Cite
|
Sign up to set email alerts
|

Laser Powder Bed Fusion of Pure Tungsten: Effects of Process Parameters on Morphology, Densification, Microstructure

Abstract: Tungsten has been widely used in many industrial fields due to its excellent properties. However, owing to its characteristics of inherent brittleness at room temperature and high melting point, it is difficult to prepare tungsten parts with high complexity via traditional methods. In the present work, tungsten samples were prepared by laser powder bed fusion. The influence of each process parameter including laser power, scanning speed, and hatch spacing on the surface morphology, densification, and microstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Wang et al [34] have also reported a reduction in lack of fusion porosity when using spherical powder instead of irregular powder under same process parameters (Figure 4). Relative densities of unalloyed tungsten above 98% have been recently achieved by LPBF of spherical powder feedstock [36][37][38][39][40][41][42][43][44][45]. The research on RF plasma spheroidization of tungsten powder has also revealed favorable effect on powder particle size as reported by Zi et al [32] and Wang et al [31].…”
Section: Feedstockmentioning
confidence: 89%
See 2 more Smart Citations
“…Wang et al [34] have also reported a reduction in lack of fusion porosity when using spherical powder instead of irregular powder under same process parameters (Figure 4). Relative densities of unalloyed tungsten above 98% have been recently achieved by LPBF of spherical powder feedstock [36][37][38][39][40][41][42][43][44][45]. The research on RF plasma spheroidization of tungsten powder has also revealed favorable effect on powder particle size as reported by Zi et al [32] and Wang et al [31].…”
Section: Feedstockmentioning
confidence: 89%
“…The result is immediate and seamless grain growth across the solidliquid interface [40,49]. A number of publications have also reported successful LPBF of tungsten (W) on compositionally different substrates such as steel [33,38,42,53,54] and titanium [48]. The presence of compositional difference between the liquid and solid phases in such cases is expected to impose a nucleation energy barrier and hinder the spread of molten metal on the substrate, leading to insufficient wetting.…”
Section: Substratementioning
confidence: 99%
See 1 more Smart Citation
“…Tungsten and its alloys have been used for many engineering applications such as in the aerospace, automotive, nuclear energy, materials processing, and defense industries. They are also considered attractive materials for high-temperature applications such as heating elements, rocket nozzles, heat shields, and combustion chambers [ 1 , 2 , 3 ]. This is due to the superior properties of tungsten such as high melting point (3420 °C), high thermal conductivity, high tensile strength, and high hardness [ 1 , 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are also considered attractive materials for high-temperature applications such as heating elements, rocket nozzles, heat shields, and combustion chambers [ 1 , 2 , 3 ]. This is due to the superior properties of tungsten such as high melting point (3420 °C), high thermal conductivity, high tensile strength, and high hardness [ 1 , 2 , 3 , 4 , 5 ]. In addition, due to its excellent radiation shielding properties, tungsten is also considered a promising plasma-facing material for future nuclear fusion reactors [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%